Stability of thin plates with compressible material in the theory of elastic-plastic processes - Dung, Dao Van (Vietnam Journal of Mechanics, 1995)
In this paper is given a system of stability equations of elastic-plastic thin plates made of compressible material. These stability equations are a generalization of ones in the theory of elasticity and the simple processes theory.